Strategi Penguatan Karakter Religius Melalui Pembiasaan Sholat Dhuha dan Pembacaan Surah Al-Kahfi Bersama di SMK YPF Bandung - Afriansyah, Ardi; Sundawa, Dadang; Komalasari, Kokom; Komariyah, Siti (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to explore the strategies implemented by SMK YPF Bandung to enhance students' religious character. The school conducts regular activities, including Dhuha prayers and Surah Al-Kahfi recitations, but faces several challenges in their execution. Employing a qualitative case study approach, the researchers conducted interviews, observations, and document analysis, with school staff and students as primary data sources. Findings reveal that these routine activities not only serve as acts of worship but also function as character-building tools, fostering traits like discipline, responsibility, and leadership among students. However, the school encounters challenges, such as maintaining student discipline and consistency, limited facilities and infrastructure, varying levels of students’ Qur'anic reading proficiency, and environmental influences, all of which hinder character development efforts. The study concludes that consistent engagement in Dhuha prayers and Surah Al-Kahfi recitations positively impacts students’ development into individuals with integrity, well-prepared to enter the workforce with strong ethical and moral values. This research is limited by its focus on a single school, meaning that the findings may not fully represent conditions in other schools.